2013
DOI: 10.1517/17425247.2013.769956
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ϵ-caprolactone) microcapsules and nanocapsules in drug delivery

Abstract: Microencapsulation is a well-established process in pharmaceutical industry to protect drugs from chemical degradation and to control drug release. In this context, PCL is a useful polymer to prepare microcapsules. Nanoencapsulation, a more recent approach, offers new possibilities in drug delivery. PCL can be used as polymer to prepare different types of nanocapsules presenting diverse flexibility according to the chemical nature of the core. Those nanocapsules are capable of controlling drug release and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(119 citation statements)
references
References 92 publications
5
103
0
2
Order By: Relevance
“…The LNCs are composed of an organogel as oily core surrounded by a biodegradable polymeric wall, in which dispersion in water is guaranteed by surface coating with polysorbate 80 micelles. 29 Oral administration of LNC or AcE-LNC, but not AcE, did not cause any toxicity and inhibited the melanoma development. In vitro studies showed that LNC or AcE-LNC caused late apoptosis and necrosis, as well as cell cycle arrest in SK-Mel-28 cells.…”
Section: Introductionmentioning
confidence: 89%
“…The LNCs are composed of an organogel as oily core surrounded by a biodegradable polymeric wall, in which dispersion in water is guaranteed by surface coating with polysorbate 80 micelles. 29 Oral administration of LNC or AcE-LNC, but not AcE, did not cause any toxicity and inhibited the melanoma development. In vitro studies showed that LNC or AcE-LNC caused late apoptosis and necrosis, as well as cell cycle arrest in SK-Mel-28 cells.…”
Section: Introductionmentioning
confidence: 89%
“…This polymer was chosen because it has been approved by the Food and Drug Administration (FDA) for drug delivery specific applications and has prior been used for nanoparticle preparation [17,[22][23][24]. Concentrations of components of the three nanocarriers are given in Table 1.…”
Section: Preparation Of Nanoparticlesmentioning
confidence: 99%
“…In the specific case of PBCA NPs, drug release could be the consequence of either particle disintegration due to surface erosion, drug diffusion through the polymeric matrix, or both (30,32). Whereas, with respect to PCL NPs, 5-FU release during this second phase could be due to drug diffusion through the polymeric matrix as opposed to polymer disintegration, which for PCL is a very slow process in an aqueous medium given its considerable hydrophobic character (18,31,33).…”
Section: Discussionmentioning
confidence: 99%
“…and Poly(ε-caprolactone) Nanoparticles 5-FU release at pH 7.4 from PBCA (and PCL) NPs showed a biphasic process, typical of these polymers (18,(30)(31)(32)(33). Such a sustained drug-release profile was characterized by an initial rapid (burst) 5-FU release phase (up to ≈27% and ≈16% in from PBCA NPs and PCL NPs in 3 h, respectively), with the remaining 5-FU molecules being released in a more sustained manner (over a period of 93 and 117 h from PBCA NPs and PCL NPs, respectively) (Fig.…”
Section: -Fluorouracil Release From Poly(butylcyanoacrylate)mentioning
confidence: 99%